A misplaced intramuscular injection and limb-threatening ischemia - Sarkar, Sumantra (J Family Med Prim Care, 2017)
Femoral artery thrombosis is a rare complication of intramuscular (IM) injection in children. A 12-month-old boy presented with right lower limb ischemia and digital gangrene 3 days after an injection of ceftriaxone administered to his medial aspect of the right thigh. Successful thrombolysis and partial limb salvage was possible with enoxaparin despite a late presentation. Unnecessary and unsafe IM injection in community practice might lead to such devastating outcome which should be avoided.